Preparation of Molecularly Imprinted Polymer and Its Recognition Property for Acetanilide - Fan, Shunli; Cheng, Yaqun; Luo, Ruxin; Huo, Jing'e (Asian Journal of Chemistry, 2014)
Molecularly imprinted polymers with highly selective recognition for acetanilide were prepared by precipitation polymerization using acetanilide as template molecule, methacrylic acid as functional monomer and ethylene glycol dimethaerylate as crosslinker. The experiment measured the influence of the molar ratio of the template molecule and the functional monomer upon the adsorption capacity of the polymers and the optimized ratio was obtained to be n(acetanilide) : n(methacrylic acid) = 1:4. Scatchard analysis indicated the imprinted polymer acetanilide template molecule and functional monomer methacrylic acid formed one kind of binding site, binding site dissociation constant KD = 4.35 mmol/L, the apparent maximum binding capacity Qmax = 111.87 μmol/g.